Recovery of Recombinant Canine Distemper Virus That Expresses CPV-2a VP2: Uncovering the Mutation Profile of Recombinant Undergoing 50 Serial Passages In Vitro - Liu, Fuxiao; Lin, Jiahui; Wang, Qianqian; Zhang, Youming; Shan, Hu (Frontiers in Cellular and Infection Microbiology, 2022)
Canine distemper and canine parvoviral enteritis are infections caused by the canine distemper virus (CDV) and canine parvovirus type 2 (CPV-2), respectively. They are two common infectious diseases that cause high morbidity and mortality in affected dogs. Combination vaccines have been broadly used to protect dogs from infections of CDV, CPV-2, and other viruses. VP2 is the most abundant protein of the CPV-2 capsid. It elicits potent immunity in animals and, therefore, is widely used for designing subunit antigen-based vaccines. In this study, we rescued a recombinant CDV (QN vaccine strain) using reverse genetics. The recombinant CDV (rCDV-VP2) was demonstrated to express stably the VP2 in cells for at least 33 serial passages in vitro. Unfortunately, a nonsense mutation was initially identified in the VP2 open reading frame (ORF) at passage-34 (P34) and gradually became predominant in rCDV-VP2 quasispecies with passaging. Neither test strip detection nor indirect immunofluorescence assay demonstrated the expression of the VP2 at P50. The P50 rCDV-VP2 was subjected to next-generation sequencing, which totally identified 17 single-nucleotide variations (SNVs), consisting of 11 transitions and 6 transversions. Out of the 17 SNVs, 1 and 9 were identified as nonsense and missense mutations, respectively. Since the nonsense mutation arose in the VP2 ORF as early as P34, an earlier rCDV-VP2 progeny should be selected for the vaccination of animals in future experiments.